2018
DOI: 10.1097/md.0000000000010250
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with HIV infection among Yi minority residents in Liangshan Prefecture, Sichuan Province

Abstract: We aimed to evaluate HIV prevalence among residents of Liangshan Prefecture through HIV sentinel surveillance (HSS) data over the period from 2010 to 2016, and investigate risk factors for HIV infection in this population and interactions among them.Two sites (Dechang and Ningnan counties) with majority-Han populations, and 1 site (Butuo) with a majority-Yi population were selected. We used questionnaires to investigate residents’ demographic and behavioral characteristics from 2010 to 2016, and performed HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…The mechanisms underlying HIV are complex, and the symptoms are changeable. However, consistent with the previous studies (Yang et al, 2017; Yang et al, 2018), our results showed that most Yi family caregivers with a lower education level, most of them were illiterate. Limited educational levels could have led to a lack of HIV knowledge (Hoang et al, 2019), and caregivers could have relied on care experience that was accumulated gradually during the process of caring for PLWH.…”
Section: Discussionsupporting
confidence: 93%
“…The mechanisms underlying HIV are complex, and the symptoms are changeable. However, consistent with the previous studies (Yang et al, 2017; Yang et al, 2018), our results showed that most Yi family caregivers with a lower education level, most of them were illiterate. Limited educational levels could have led to a lack of HIV knowledge (Hoang et al, 2019), and caregivers could have relied on care experience that was accumulated gradually during the process of caring for PLWH.…”
Section: Discussionsupporting
confidence: 93%
“…However, the resistance rate was lower than those in Kenya and Mexico, where PDR rates were reported to be 21.9% and 15.5% [ 46 , 47 ], respectively. Many factors, including poor compliance with medication and lack of testing for baseline resistance [ 48 , 49 ], may be among the major reasons for the increase in PDR in Liangshan. Several studies have shown that HIV-1-infected individuals with drug resistance can affect treatment responses to first-line ARV therapies [ 35 , 50 - 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, research on condom use among men has mainly been conducted in Asian countries such as Cambodia [ 19 ], China [ 20 , 21 ], India [ 22 – 24 ], Singapore [ 25 ], Indonesia [ 26 ], with a few focusing on Middle East [ 1 ] and Africa [ 27 , 28 ]. Generally, such studies have revealed the predictors of consistent condom use among homosexual males [ 19 , 27 , 29 ], young dating adults [ 30 ], and men who patronize paid sex [ 22 ].…”
Section: Introductionmentioning
confidence: 99%